Web Based Employee Attendance System Using RAD Method: Sistem Kehadiran Karyawan Berbasis Web Menggunakan Metode RAD - Saesar Joko Pramono; Uce Indahyanti; Nuril Lutvi Azizah; Cindy Taurusta (Indonesian Journal of Innovation Studies, 2026)
General Background Online attendance systems have become essential in modern organizations to ensure efficient and accurate employee attendance management. Specific Background Conventional attendance methods are prone to errors and data manipulation, while existing digital systems still lack comprehensive features such as integrated monitoring and real-time validation. Knowledge Gap Many current solutions do not fully integrate location validation, facial verification, and real-time reporting within a single system to support transparent attendance management. Aims This study aims to design and develop a web-based employee attendance application using the Rapid Application Development method to provide a more comprehensive and flexible solution. Results The developed SarAbsensi system integrates GPS-based location validation, photo verification, and real-time data processing, achieving functionality of 81.2%, reliability of 77%, usability of 80.8%, and efficiency of 86%, with an overall score of 81.2% categorized as very good. Novelty The system combines multiple validation mechanisms and real-time reporting features within a RAD-based development framework to support transparent and structured attendance management. Implications The application supports accurate attendance recording, facilitates monitoring by administrators, and provides a structured basis for organizational decision-making related to employee attendance and performance. Keywords: Online Attendance, Rapid Application Development, Web System, Employee Monitoring, Real Time Validation Key Findings Highlight Integration of location and photo verification ensures valid attendance recording System usability and efficiency achieved high evaluation scores across testing aspects Real-time reporting supports structured monitoring by administrators